ANALYSIS OF RICE MARKETING EFFICIENCY IN EAST OGAN KOMERING ULU TIMUR - Khairunnisa Ramadini; Ratna Winandi; Wahyu Budi Priatna (Socio-Economics/Agribusiness Department, 2022)
Rice is the main food commodity that affects the Indonesian people's welfare. Thus, it is more complex to replace rice with other food commodities. This large rice production requires post-production handling through a good marketing process because it can increase farmers income. This research aims to analyze the efficiency of rice marketing in East Ogan Komering Ulu Timur Regency through marketing channels, market structure, market conduct, and market performance. This research was by taking 90 respondents of rice farmers using a simple random sampling method. Furthermore, to determine the respondents' marketing agency, it used the snowball sampling method by following the path of the farmers. Based on the results of the research, there were four rice marketing channels formed, the first was farmers - Gapoktan factories - wholesalers - retailers - consumers, the second was farmers - Gapoktan factories - consumers, the third is farmers - millers - retailers - consumers, and the fourth was a farmer – miller – consumer. Hence, marketing channel 2 was the most efficient, because it has a low marketing margin value, and has a farmer's share value, and a high-cost benefit ratio.